2022
DOI: 10.37249/assalam.v6i2.405
|View full text |Cite
|
Sign up to set email alerts
|

Cambodian Buddhist Monk Students’ Motivation in Learning English: The Case of Hun Neng Buddhist Primary School, Kampong Cham Town

Abstract: This study presents an overview of a survey on Cambodian Buddhist monk students’ motivation in learning English at Hun Neng Buddhist Primary School, Kampong Cham Town. The study employed a quantitative method. The study aimed to examine the motivation levels of the participants and the difference between intrinsic and extrinsic motivation levels. 93 Buddhist monk students participated in the study. The findings show that the Buddhist monk students were highly motivated to learn English, and it was also reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 24 publications
(27 reference statements)
0
3
0
Order By: Relevance
“…In the Cambodian context, two current studies were conducted and found similar results. The first one was conducted by Keo et al (2022) at a Buddhist primary school and found that the Buddhist monk students were more extrinsically motivated, and the second one was conducted with 265 high school students by Sor et al (2022) and found the high school students were more extrinsically motivated to learn English as a foreign language. These two studies also revealed the same thing: the participants had high motivation to learn English.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Cambodian context, two current studies were conducted and found similar results. The first one was conducted by Keo et al (2022) at a Buddhist primary school and found that the Buddhist monk students were more extrinsically motivated, and the second one was conducted with 265 high school students by Sor et al (2022) and found the high school students were more extrinsically motivated to learn English as a foreign language. These two studies also revealed the same thing: the participants had high motivation to learn English.…”
Section: Discussionmentioning
confidence: 99%
“…But, in Cambodia, Keo et al (2022) conducted a study with 93 Buddhist monk students learning English as a foreign language at a Buddhist primary school in Kampong Cham town and found that those Buddhist monks had high motivation toward learning English, and they were more extrinsically motivated than intrinsically.…”
Section: Some Previous Studies Of Motivation In Learning Englishmentioning
confidence: 99%
“…Following the tumultuous events of the Khmer Rouge regime and the subsequent period of reconstruction and nation-building, Cambodia gradually shifted its focus towards rebuilding its education system and positioning itself within the global community [13]. The increasing importance of English as a global lingua franca has led to its growing prominence in Cambodian society and education [14].…”
Section: Literature Reviewmentioning
confidence: 99%
“…While urban areas and well-established institutions may have better access to English language instruction, rural and under-resourced schools often face shortages of qualified English teachers and teaching materials [20]. As a result, efforts are being made to provide professional development opportunities for English teachers and to expand access to quality English language learning resources for schools in all regions of Cambodia [14].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The result shows that every student has two types of motivation, namely internal motivation that students get from themselves who have a strong desire to achieve their goals, and external motivation that students get from their environment, for example, lecturers, friends, or family. Another research proposed by Keo et al (2022) reviewed the motivation of Cambodian Buddhist monk students in learning English at Hun Neng Buddhist Primary School, Kampong Cham City, and found that 93 Buddhist monk students were highly motivated to learn English extrinsically rather than intrinsically.…”
Section: Student Motivation In Learning Bahasamentioning
confidence: 99%